ORGANIC FARMING AS A FACTOR OF EUROPEAN INTEGRATION OF UKRAINE - Кузьменко, О. Б. (Scientific Progress & Innovations, 2013)
The necessity of the development of organic farming in Ukraine, as a condition of growth of exports of agricultural products to the European Union was grounded. That at the same time ensures the preservation and reproduction of the qualitative characteristics of land resources. It is proved that the trend of demand for organic products in the European Union and the available high-quality and environmentally friendly land resources in Ukraine create the preconditions for enhancing organic production and corresponding exports. The problems hindering the implementation of the farming system and proposals for their solution were defined.